The recovery properties under load of a shape memory polymer composite material. Issue 12 (17th December 2019) - Basit, A.; L'Hostis, G.; Durand, B.
Abstract: In many applications, shape memory alloys are being replaced by shape memory polymers as they have some better properties than shape memory alloys. Nevertheless, shape memory alloys can recover under load which shape memory polymers cannot. Shape memory polymers are not capable of giving full recovery even lifting a tiny load. The melting temperature or the glass transition temperature is the transition temperatures to which shape memory polymers are closely heated. Then a deforming force up to a certain position is applied to the heated shape memory polymers. After that shape memory polymer is permitted to cool while keeping it deformed. After the cooling, shape memory polymer obtains the temporary shape which can be recovered by reheating it at the similar transition temperature (glass transition or melting). Consequently, it recovers at its initial state. Shape memory polymer can achieve constrained recovery and unconstrained recovery, nonetheless; under stress, it is partly recovered. In current work, recovery under load has been investigated of an asymmetrical shape memory composite. It is established that it is capable to recover under various loads. Under various loads, it shows full recovery in reference to initial state. The ability to recover under load can be potentially used in diverse applications.